Association between High-Density Lipoprotein Cholesterol to Apolipoprotein A-I Ratio and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study - Hangkai Huang; Jinghua Wang; Lei Xu; Min Miao; Chengfu Xu (International Journal of Endocrinology)
Background. This study aimed to explore the association between high-density lipoprotein cholesterol to apolipoprotein A-I ratio (HDL-C/apo A-I) and nonalcoholic fatty liver disease (NAFLD). Methods. A total of 9025 Chinese adults were enrolled in this cross-sectional study, who presented their annual health checkups at Zhenhai Lianhua Hospital, Ningbo, during 2017. Results. The NAFLD prevalence was 33.7%, and HDL-C/apo A-I was significantly decreased in NAFLD patients, as well as in lean NAFLD and in patients with NAFLD-related advanced fibrosis (all P<0.001). The prevalence of NAFLD and components of metabolic syndrome are inversely associated with HDL-C/apo A-I (P<0.001). Multivariate logistic regression analysis show that HDL-C/apo A-I is inversely associated with the risk of NAFLD (odds ratio: 0.353, 95% confidence interval: 0.257–0.486; P<0.001). Conclusions. Our results suggested that increased HDL-C/apo A-I is significantly associated with a decreased risk of NAFLD.